Editorial: Extreme events and risk of hazards: perspectives from observations and modeling - Gomes, Helber Barros; Herdies, Dirceu Luis; Baltaci, Hakki; Juneng, Liew (Frontiers Media Sa, 2023)
[No abstract available]
Keywords: extreme events; climate change; landslides; droughts; floods